Complex Evaluation of Antioxidant Capacity of Milk Thistle Dietary Supplements - Jitka Viktorova; Milena Stranska-Zachariasova; Marie Fenclova; Libor Vitek; Jana Hajslova; Vladimir Kren; Tomas Ruml (MDPI AG, 2019)
Numerous in vitro assays are used to characterize the antioxidant properties of natural-based matrices. However, many of them generate contradictory and non-compliant results. In our study, we focused on the characterization of traditionally used biochemical (2,2′-azino-bis-(3-ethylbenzothiazoline-6 sulfonic acid) (ABTS), Oxygen Radical Absorption Capacity (ORAC), and 2,2-diphenyl-1-picrylhydrazyl (DPPH)) and cellular (CAA) antioxidant tests on a broad set of milk thistle dietary supplements containing silymarin. In addition to 26 commercially available preparations, also the natural silymarin extract available from Sigma Aldrich, St. Louis, MI, USA, and a model mixture of pure flavonoid/flavonolignans mimicking the silymarin composition were investigated as control samples. Significant differences in the antioxidant capacity of the supplements were observed. Unlike the DPPH, the results of the ABTS and ORAC methods correlated with the silymarin components determined by U-HPLC-HRMS/MS. The responses in CAA were considerably lower than in other assays. Silymarin exhibited a significantly higher antioxidant capacity than the artificially prepared flavonoid/flavonolignans mixture in all tests, indicating possible presence of other antioxidants of natural origin. The follow-up U-HPLC-HRMS/MS screening revealed the presence of tens of non-silymarin compounds with reported antioxidant activity (not only in the silymarin extract, but also in the milk thistle preparations). The sum of the total phenolics and the sum of the simple phenolics correlated with CAA results more than silymarin.